PARENT IDENTIFICATION IN A MULTI LOCATION TRIAL SEED ORCHARD OF ACACIA MANGIUM USING MICROSATELLITE MARKERS - Nurtjahjaningsih, I. L. G. (Secretariat of Forestry Research and Development Agency, 2016)
Parent gametes contribution is one of the important factors that affect on differences of morphologies/ phenotypic of individual tree in a seed orchard. Morphological variations plus trees observed in an opened pollination seed orchard of A. mangium. Parent trees that produce good performance offspring should be identified to increase the efficiency of tree improvement strategies of this species. Thus, aims in this study were to assess mating system and to identify parental trees within a single population first generation SSO that resulted good growth character in a multi location trial of A. mangium. This study was conducted in two types of seed orchard i.e. a single population (SP) F1 and a multi location trial (MLT) plot E of A. mangium at Wonogiri (Central Java). Using ten microsatellite markers for A. mangium, parental analysis was conducted with comparing genetically between plus trees in the SP as a parent trees and thirty two the best rank plus trees in MLT as an offspring and analyzed using program Cervus ver.3.03. Results showed that the plus trees in the MLT orchard originated from various parent gametes contribution in the SP seed orchard. Moreover, the best rank plus trees dominantly originated from single pair between maternal and paternal trees. However, another pollination behavior, a maternal tree was pollinated by two paternal trees. Moreover, a paternal tree pollinated several maternal trees. Similar flowering characteristic of individual trees that originated from same provenance might be responsible to the pattern of mating system in the opened pollination seed orchard. From the results, efficiency on seed orchard management might be proposed.